PENGARUH PROFITABILITAS, STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Levina Clarinda Clarinda; Liana Susanto; Syanti Dewi (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
Susanto, dan Syanti Dewi Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, Jakarta *Email: levinaclarinda99@gmail.com Abstract: The purpose of this study is to obtain empirical evidence on the effect of profitability, capital structure, firm growth, and firm size on firm value manufactured companies listed in Indonesian Stock Exchange during 2017-2019. The sampling method used is purposive sampling with total sample 46 data. Data processing techniques using multiple regression analysis what help by Eviews 11.0. The results of this study showed that profitability, capital structure, firm growth do not have a significant effect on firm value, while firm size has a significant negative effect on firm value. The implication of this study is the need to used a balanced capital structure to increase firm value